Radiological Liver Volumetry and its Impact on Surgical Decision-Making and Post-Hepatectomy Liver Failure. A Clinical Study - ALI, RABIAA MAHMOOD; ATIQ, MUHAMMAD; BODLA, MARIA AFZAL; HASSAN, MUHAMMAD HABIB; SHERWANI, UMAIR KHAN; MAHMOOD, SIDRAH (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post hepatectomy liver failure (PHLF) has been an important morbidity and mortality cause after liver resection. The preoperative evaluation of the hepatic reserve must be accurately conducted to ensure the correct planning of the surgery and elimination of postoperative complications. Radiological liver volumes have become a useful method to predict future liver remnant (FLR) and maximize surgeries. Objective: To assess how radiological liver volumetry can influence the surgical planning and its correlation with the occurrence of post-hepatectomy liver failure in patients that undergo elective hepatectomy. Methods: This was a prospective clinical trial study where 100 patients undergoing an elective liver resection surgery at a tertiary care unit were included. Preoperative contrast-enhanced computed tomography-based liver volumetry was carried out on all patients to determine the total liver volume, planned resection volume and FLR. In making decisions in surgery relating to the degree of hepatectomy, volumetric findings were used in conjunction with clinical and biochemical parameters. The liver functions after the surgery were controlled, and PHLF was evaluated according to the standard criteria. The statistical associations were used to determine the relationship between FLR and PHLF. Results: As an average, the liver remnant was found to be 62.3 ± 9.8. Forty-six percent of the patients had major hepatectomy, and 54 percent minor resections. A liver failure post- hepatectomy was seen in 18 percent of the patients with majority being mild to moderate cases. Patients who suffered FLR <60% showed a high incidence of PHLF than those who suffered FLR ≥60% (38.9% vs. 6.3, p < 0.05). Postoperative liver failure had strong relationships with lower FLR values and intrinsic chronic liver disease. Conclusion: Radiologic liver volumetry is important and dependable preoperative risk stratification and surgical planning tool in hepatectomy. Proper evaluation of the future liver remnant would greatly decrease future hepatectomy liver failure and would help to develop personalized and safer hepatic surgery.